Олександр Білецький, якого не знаємо - Гаврилюк, Н. (Слово і Час, 2009)
У статті розглянуто вірші О. Білецького “Нарцис” і “Новий Нарцис”. Здійснено спробу простежити
спільне і відмінне в зіставленні з міфологічним сюжетом. Стверджується, що Нарцис у трактуванні
О. Білецького – це визначальна метафора неоднозначності людської психіки, шляху від егоїзму до
каяття, шляху самопізнання. In this article, we analyse O.Biletsky’s poems “Narcissus” and “New Narcissus”, in order to find out their
similarities and differences with the mythical plot. Thus, we argue that in O.Biletsky’s poems the figure of
Narcissus is used as a metaphor of ambiguity of human psyche, or, in other words, of a way from egoism to
repentance, the way of self-discovery. В статье рассмотрены стихотворения О. Белецкого “Нарцисс”
и “Новый Нарцисс”. Осуществлена попытка проследить общее
и отличное в сопоставлении с мифологическим сюжетом.
Утверждается, что Нарцисс в трактовке О. Белецкого – это
определяющая метафора неоднозначности человеческой
психики, пути от эгоизма к раскаянию, пути самопознания.